2021
DOI: 10.2147/ppa.s302818
|View full text |Cite
|
Sign up to set email alerts
|

Home Care Patients’ Experiences with Home Care Nurses’ Support in Medication Adherence

Abstract: Purpose To describe nurses’ support interventions for medication adherence, and patients’ experiences and desired improvements with this care. Patients and Methods A two-phase study was performed, including an analysis of questionnaire data and conducted interviews with members of the care panel of the Netherlands Patients Federation. The questionnaire assessed 14 types of interventions, satisfaction (score 0–10) with received interventions, needs, experiences, and desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…These results reflect those of Dijkstra et al (2021), who also found that supportive nursing interventions positively affect medication adherence. In this qualitative study, the participants were satisfied with the intended intervention but wanted to receive more services [40]. Also, These results are consistent with data obtained in Gwadry-sridhar et al 2016) also investigated the effect of a multidisciplinary self-care management program on the adherence of renal patients to antihypertensive treatment, and they reached the same results as the present study [42].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results reflect those of Dijkstra et al (2021), who also found that supportive nursing interventions positively affect medication adherence. In this qualitative study, the participants were satisfied with the intended intervention but wanted to receive more services [40]. Also, These results are consistent with data obtained in Gwadry-sridhar et al 2016) also investigated the effect of a multidisciplinary self-care management program on the adherence of renal patients to antihypertensive treatment, and they reached the same results as the present study [42].…”
Section: Discussionsupporting
confidence: 85%
“…These results reflect those of Dijkstra et al (2021), who also found that supportive nursing interventions positively affect medication adherence. In this qualitative study, the participants were satisfied with the intended intervention but wanted to receive more services [ 40 ]. Also, These results are consistent with data obtained in Gwadry-sridhar et al (2005) and Heloue et al(2016).…”
Section: Discussionmentioning
confidence: 99%
“…The medication management patterns of one-third of the sample potentially increased their risks of an MRP (using potentially inappropriate medicines, drug-drug interactions, hospitalisation) by self-treatment with unprescribed over-the-counter medication, as previously reported by Jin 38 . Most of our home-dwelling older adults were polymedicated but nevertheless managed their medication without regular support from informal or professional caregivers, although this increases the risks of errors, compliance issues and suboptimal medication management 39 . Our ndings showed that one-fth of the sample presented with moderate cognitive impairment, often associated with an increased risk of non-adherence, which can lead to poor therapeutic outcomes, greater risks of MRPs and poor medication management, as reported in the systematic review by Kröger 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, patients with chronic conditions report higher adherence and persistence with treatment, confident self-management, and lower total costs with nurse support, medication reminders, injection training, and pen disposal [ 16 ]. Moreover, nurse support improves patient self-management of treatment recommendations and enables patients to discuss their adherence problems with healthcare [ 17 ].…”
Section: Introductionmentioning
confidence: 99%